Medical Applications of Artificial Intelligence: Chapter 20 A Crash Introduction to Ambient Assisted Living. - Fernández-Carmona, Manuel; Urdiales-García, Amalia Cristina (Taylor & Francis, 2013)
Ambient intelligence (AmI) was coined as a term by the European Commission, as discussed in the work of (Ducatel et al. 2001), and has received major attention in the last decade. An AmI environment is expected to be sensitive to the needs, personal requirements, and preferences of its inhabitants and capable of anticipating their needs and behavior to interact with people in a user-friendly way (Sadri 2011). There are many similar definitions, but most authors agree that all of them imply the capability of embedding sensors in everyday objects to raise context awareness and processors to learn and adapt to the user’s behavior (Aarts et al. 2002; Gaggioli 2005).
Keywords: Inteligencia artificial - Aplicaciones médicas; Ambient intelligence